The Use of Physical Factors in Rehabilitation of Children with Hip Dysplasia - N.G. Nikolayeva; L.B. Eliy (Zaslavsky O.Yu., 2012)
The review of the literature on physical therapy for children with hip dysplasia is presented. The analysis of the results of the use of traditional methods of physical therapy, as well as innovative techniques for children with hip dysplasia, associated with connective tissue dysplasia and perinatal pathology of the central nervous system, is given.